General practitioners’ perceptions on opportunistic single-time point screening for atrial fibrillation: A European quantitative survey - Vermunicht, Paulien; Grecu, Mihaela; Deharo, Jean-Claude; Buckley, Claire M.; Palà, Elena; Mairesse, Georges H.; Farkowski, Michal M.; Bergonti, Marco; Pürerfellner, Helmut; Hanson, Coral L.; Neubeck, Lis; Freedman, Ben; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: There is no clear guidance on how to implement opportunistic atrial fibrillation (AF) screening in daily clinical practice. Objectives: This study evaluated the perception of general practitioners (GPs) about value and practicalities of implementing screening for AF, focusing on opportunistic single-time point screening with a single-lead electrocardiogram (ECG) device. Methods: A descriptive cross-sectional study was conducted with a survey developed to assess overall perception concerning AF screening, feasibility of opportunistic single-lead ECG screening and implementation requirements and barriers. Results: A total of 659 responses were collected (36.1% Eastern, 33.4% Western, 12.1% Southern, 10.0% Northern Europe, 8.3% UK & Ireland). The perceived need for standardized AF screening was rated as 82.7 on a scale from 0 to 100. The vast majority (88.0%) indicated no AF screening program is established in their region. Three out of four GPs (72.1%, lowest in Eastern and Southern Europe) were equipped with a 12-lead ECG, while a single-lead ECG was less common (10.8%, highest in UK & Ireland). Three in five GPs (59.3%) feel confident ruling out AF on a single-lead ECG strip. Assistance through more education (28.7%) and a tele-healthcare service offering advice on ambiguous tracings (25.2%) would be helpful. Preferred strategies to overcome barriers like insufficient (qualified) staff, included integrating AF screening with other healthcare programs (24.9%) and algorithms to identify patients most suitable for AF screening (24.3%). Conclusion: GPs perceive a strong need for a standardized AF screening approach. Additional resources may be required to have it widely adopted into clinical practice.